HIV knowledge and its influence on prevention practices among females aged 15-24 years in Kisumu East Sub-County, Kenya - Odero, Tabitha Adhiambo; Owek, Collins James; Machera, Tom Marwa (Pan African Medical Journal, 2025)
Introduction: globally, approximately 39 million people live with HIV/AIDS, with females accounting for 54%. In Kenya’s Kisumu County, HIV prevalence is 3.5 times the national average and disproportionately affects females. By 2022, it ranked 4th nationally for new infections among 15-24-year-olds, with HIV-related mortality over 20% higher in females. Comprehensive HIV knowledge remains low, especially in Kisumu’s rural and informal areas. The objective was to assess HIV knowledge and its influence on prevention practices among females aged 15-24 in Kisumu East Sub-County. Methods: a cross-sectional mixed-methods study was conducted among 404 females aged 15-24 using multistage cluster sampling. Quantitative data were analyzed in R (v4.3.1) using descriptive statistics, chi-square tests, and logistic regression. For qualitative data, 15 in-depth interviews were purposively sampled and thematically analyzed using the Health Belief Model. Results: the mean HIV knowledge score was 10.75/16 (SD = 2.97); participants were classified into low (≤8; 15.1%), moderate (9-12; 52.5%), and high (≥13; 32.4%) knowledge groups based on their scores. Higher knowledge was significantly associated with awareness of own (OR = 3.87, CI: 2.15-6.97) and partner's HIV status (OR = 6.82, CI: 3.78-12.31), and knowledge of PrEP/PEP (p < 0.01). However, high knowledge was linked to lower odds of abstinence (OR = 0.28, p = 0.001) and consistent condom use (OR = 0.32, p = 0.03). Peer pressure, cited by 63%, was the most perceived barrier. Conclusion: HIV knowledge alone is insufficient. Prevention must integrate peer-led education, behavioral support, and youth-friendly services to bridge the knowledge-behavior gap.
Keywords: HIV knowledge; influence; prevention practices; females